A new compsocid booklouse from the Cretaceous amber of Myanmar (Psocodea: Troctomorpha: Amphientometae: Compsocidae). (31st December 2016) - Azar, Dany; Hakim, Marina; Huang, Diying
Abstract: Paraelectrentomopsis chenyangcaii gen. et sp. nov. from the Cretaceous Burmese amber is characterized, described, illustrated and its position is discussed. This fossil taxon is the second compsocid barklouce to be described from the Burmese amber and constitute one of the earliest records of the family. A checklist of known Compsocidae is given. Identification keys of all known Compsocidae are provided. A palaeobiogeography scenario is proposed.